Atrial fibrillation with flutter episode in patient with mitral stenosis - Deri Arara; Yerizal Karani (Majalah Kedokteran Andalas, 2018)
Mitral stenosis (MS) is a condition which happened because of congenital or acquired event. The most common etiology of MS in Indonesia is Rheumatic Heart Disease (RHD). Chronic inflammation on the mitral valve could lead to stenosis from mild to severe degree. Mitral stenosis could lead to many complications such as pulmonary hypertension and atrial fibrillation (AF). The prevalence of AF in patients with MS is related to the severity of valve obstruction and patient age. AF event in patient with MS could be happen because of Left Atrial (LA) dilatation of the patient. The mechanism that responsible for AF in patient with MS is a complex one. AF even with or without atrial flutter episode could lead a deterioration of patient hemodynamic. In the other way, the patient also predisposes to left atrial thrombus formation and systemic embolic events. Good awareness in diagnosis and management of atrial fibrillation in patient with MS are mandatory to reduce the morbidity and mortality.